Beta-haemolytic streptococci in farmed Nile tilapia, Oreochromis niloticus, from Sullana-Piura, Peru - Ortega A, Yessica; Barreiro S, Frank; Tec Acui, Gina Castro S.; Huancare P, Karina; Manchego S, Alberto; Belo, Marco A. A. [UNESP]; Figueiredo, Mayra A. P.; Manrique, Wilson G.; Sandoval Ch, Nieves (Univ Cordoba, 2017)
Objective. This investigation aimed to study the presence of Streptococcus spp. in tilapia (Oreochromis niloticus) from fish farm located in Sullana-Piura, Peru. Materials and methods. 150 fish with clinical signs of streptococcal disease were sampled, and the bacterium isolation was performed on blood agar, correlated to histopathological lesions description and molecular confirmation by real-time PCR. Results. The necropsy revealed exophthalmia, hyphema, congestion and/or haemorrhagic meninges, ascites, splenomegaly, hepatomegaly and diffuse haemorrhagic zones throughout the body. 102 isolated positives (54 tilapias) to Streptococcus spp. were identified in the microbiological analysis (prevalence of 26%), the brain was the organ with the highest percentage of this bacteria (34.31%), and 19 isolates were beta-haemolytic (18.63%) with prevalence of 10.12%. Fish beta-haemolytic streptococci presented epicarditis, perisplenitis and chronic meningitis, panophthalmitis, coagulative necrosis of skeletal muscle and granulomas formation. In the confirmatory test by real-time PCR, any positive tilapia to S. iniae was obtained. The results were analysed using a stochastic simulation of beta distribution using @ Risk program uncertainty, reporting an average prevalence of 0.66% in sick tilapias. Conclusions. The analysed fishes were positive to bacteria of the genus Streptococcus, which confirms its presence in the fish farm. However, 19 isolates were beta-haemolytic, and the presence of S. iniae was not positive to the limit prevalence of 2.7% in real-time PCR.
Keywords: Cichlids; histopathology; microbiology; PCR; teleost fish